2018
DOI: 10.1016/j.jfda.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and anticancer effect of ethanolic and aqueous extracts of the roots of Ficus beecheyana and their phenolic components

Abstract: This study aimed to investigate the antioxidant and anticancer effects of ethanolic and aqueous extracts of the roots of Ficus beecheyana (EERFB and AERFB) and their phenolic components. In this study, total phenolic content and antioxidant activity of EERFB were higher than those of AERFB. Major phenolic compounds in the extracts were gallic acid, p-hydroxybenzoic acid, caffeic acid, chlorogenic acid, p-coumaric acid, and rutin; which were identified by high-performance liquid chromatography. Flow cytometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
1
30
0
3
Order By: Relevance
“…Our results corresponded with previous reports of Liu et al [20] and Zhou et al [17] who indicated that the antioxidant activity of C. paliurus varied with the geographical locations. The ethanol extracts of C. paliurus leaves showed stronger antioxidant capacity than the water extracts, which were in line with the extracts of F. beecheyana and S. chinensis [23,24]. Thus, the higher yields of bioactive compounds were likely to contribute to the stronger antioxidant property in the ethanol extracts.…”
Section: Effects Of Solvent and Geographical Origin On Antioxidant Acsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results corresponded with previous reports of Liu et al [20] and Zhou et al [17] who indicated that the antioxidant activity of C. paliurus varied with the geographical locations. The ethanol extracts of C. paliurus leaves showed stronger antioxidant capacity than the water extracts, which were in line with the extracts of F. beecheyana and S. chinensis [23,24]. Thus, the higher yields of bioactive compounds were likely to contribute to the stronger antioxidant property in the ethanol extracts.…”
Section: Effects Of Solvent and Geographical Origin On Antioxidant Acsupporting
confidence: 70%
“…Phytochemical contents, antioxidant and anticancer activities in plant extracts also vary with extraction solvents such as water, aqueous mixtures of ethanol, ethanol and methanol [21,22]. For example, antiproliferative activity on cancer cells was found in both ethanol and aqueous extracts of Ficus beecheyana and Saururus chinensis root, however the ethanol extracts showed better antioxidant activity [23,24]. The phenolic compounds, anticancer and antioxidant activities of indigo plants also varied with the extraction solvents [25].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of the extracts can be caused by the combined effect of these phenolic compounds and flavonoids; thus, it can be prevented free radical mediated diseases. It is known that rutin and quercetin, p ‐coumaric, caffeic acid and chlorogenic acid have strong antioxidant activities. Differences of polyphenol amounts among samples can be caused by harvested plants at different phenological stages.…”
Section: Resultsmentioning
confidence: 99%
“…Так, в работе Dong Y et al [15] показана высокая активность флавоноидов против клеточной линии опухолевых клеток аденокарциномы желудка человека (AGS). В литературе также имеются данные, что хлорогеновая и кофейная кислоты, входящие в состав сухого экстракта Padus Grayanae Maxim, проявляют антираковый эффект в отношении клеток лейкемии HL-60, незначительно ингибируют рост клеток AGS и практически не действуют на HepG2 [16].…”
Section: результаты и их обсуждениеunclassified